A Fire in the Belly of Hineāmaru: Using Whakapapa as a Pedagogical Tool in Education - Melinda Webber; Kapua O’Connor (Genealogy)
The numerous iwi (tribes) and hapū (subtribes) of Te Tai Tokerau (Northland) have a long whakapapa (genealogy) of influential leaders that have made a significant impact on the Māori world and beyond. However, ruinous media narratives that focus without relent on poverty, low employment, inadequate housing, and lagging educational outcomes—particularly among Māori—continue to negatively impact the ways students from this region define their identity. This paper presents a number of strengths-based narratives—focusing on tūpuna (ancestors) from Te Tai Tokerau whakapapa—that act as counter-narratives to this rhetoric. The paper discusses how these narratives can be used as powerful pedagogical tools that enhance Te Tai Tokerau Māori students’ self-efficacy, aspiration, optimism, and cultural pride, presenting them as powerful agents of their own destiny. This paper draws on data produced from a Marsden-funded study—led by Te Tai Tokerau descendents—that has collected and re-presented multifaceted hapū/iwi-based narratives that celebrate Te Tai Tokerau distinctiveness, success, history, and identity. This wider study has examined, contextualised, and celebrated diverse characteristics recurring in Te Tai Tokerau pūrākau (genealogical stories), pepeha (tribal sayings), waiata (songs), karakia (incantations), televisual materials, and written histories.